La participación ciudadana para construir capital social : análisis de las metodologías de participación en el Programa de Mejoramiento Integral de Barrios en Bogotá 2004 y 2015 (2017)
The Programa de Mejoramiento Integral de Barrios pretends to change people, in their personal sphere and in their life in community, therefore, the participatory component is very relevant to achieve the expected results. For this reason, the present document presents a study of the last three methodologies of citizen participation in the Program in Bogota, in order to evaluate them and to determine if these methodologies linked to the community and, therefore, allowed the social changes necessary to generate the sustainability of interventions, ie whether these methodologies served to create social capital. A participatory methodology for the Program is also proposed, so that it can be applied in compliance with its objectives.--Tomado del Formato de Documento de Grado.